Rate of testicular histology failure in predicting successful testicular sperm extraction - Castellano, Stefano; Tondo, Francesca; Bulbul, Ozgur; Aprea, Sabrina; Monti, Emanuela; Carnesi, Edoardo; Levi Setti, Paolo Emanuele; Albani, Elena (Frontiers in Endocrinology, 2024)
Background The management of Non-Obstructive (NOA) Azoospermia or Obstructive Azoospermia (OA) patients relies on testicular sperm extraction (TESE) followed by intracytoplasmic sperm injection (ICSI). In NOA patients the sperm recovery is successful in only 50% of cases and therefore the ability to predict those patients with a high probability of achieving a successful sperm retrieval would be a great value in counselling the patient and his partner. Several studies tried to suggest predictors of a positive TESE (e.g. FSH concentration), but most concluded that diagnostic testicular biopsy (histology) is best. Methods This is a retrospective analysis of 526 TESE patients. After the extraction of the testis, the resulting sample was immediately given to the embryologist, who examined the tubules for sperm cryopreservation. During the same procedure, a different specimen was destined to the histological analysis. The comparison between the two methodological approaches was carried out through a score. Results Concordance between TESE and testicular histology outcomes was found in 70,7% of patients; discordance was found in 29,3% of patients. Among the discordance outcomes, in approximately 95% we found at least 1 sperm in the TESE retrieval, while the histology report did not find any spermatozoa or found not enough compared to our evaluation; in only 5% of cases we did not find any spermatozoa or found not enough compared to what was detected in the testicular histology. Conclusion Based on our experience, to increase diagnostic accuracy, a larger biopsy should be sent to the histopathology laboratory; another option may be to use TESE cell suspension (the same embryologists employ for cryopreservation) for cytological evaluation of spermatogenesis.